Integrating Qualitative Content and Narrative Analysis: A Five-Step Approach - Sulakatko, Sirja (United Kingdom, 2025)
The integration of different analytical approaches allows harnessing their respective benefits. Nonetheless, the integration of varied methods is challenging, primarily due to the scarcity of comprehensive guidelines for such complex analyses. This paper introduces a five-step approach for combining two distinct research methods: qualitative content analysis and narrative analysis as a useful tool for researchers working under critical realist paradigm, or those who just wish to use both - categorizing and connecting approaches - in their research analysis. Qualitative content analysis plays a crucial role in categorizing insights from data. However, an exclusive reliance on content analysis might result in the loss of important contextual aspects associated with these insights. Consequently, narrative analysis becomes valuable, as it enables linking diverse elements in the data, such as the subject of study, its context, associated events, and identified categories. The process of combining the qualitative content analysis and narrative analysis method introduced in the current study was formulated during a doctoral research project within a critical realist paradigm, which necessitated a thorough consideration of both the subject matter and its context. In response to the absence of guidelines for combining content and narrative analysis, the author developed and tested a unique process during her research project. Employing the suggested approach of connecting content and narrative analysis can assist researchers, particularly those applying the critical realist paradigm in the process of generating contextually situated yet generalisable results. From a practical standpoint, innovative research methods and more comprehensive insights from academic studies enhance our understanding of various patterns in the business and management landscape.
Proceedings of the 23rd European Conference on Research Methodology for Business and Management Studies